Língua, cultura e identidade em contexto de línguas em contato no município de Missal - Unser, Otaviana Aparecida Baseggio (2006)
This study approaches the linguistic phenomenon, ethnic and cultural of languages in contact social linguistic context of the Municipal district of Missal, in the Extreme-West of the State of Paraná. This is an ethicnografic study based social linguistic that presents a situation of linguistic minority with a high degree of bilingualism, German/Portuguese. In that context based in the participants' depositions, analysis of historical and current material, we will make a study of the language, culture and the identity participants research. Missal has as main characteristic Its population in most formed by german descendants. The objective of this work is to do a study of the languages situation in contact, German/Portuguese and the linked culture of the these languages, in the social linguist context of Missal, not a specific analysis of the German language, but of the social and culture practices of the residents', where the language and the German culture are present. The researched group presented a significant index of German use in the communications. The study showed that the cultural acts influence and they promote the propagation of the use of the German language. We proved, starting from the collected data and analysis done that the local identity is structured starting from the language and culture that involves her.